Efficacy and safety of low-frequency repetitive transcranial magnetic stimulation for bipolar depression: a study protocol for a multicenter, double-blind, randomized, sham-controlled trial - Takamasa Noda; Masako Nishikawa; Yuki Matsuda; Daisuke Hayashi; Shinsuke Kito (Frontiers in Psychiatry)
IntroductionBipolar disorder has a long depressive episode and high risk of suicide. In clinical practice, patients often show no response to pharmacotherapy, which results in prolongation of the depressive episode. Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive technique expected to serve as a treatment option for bipolar depression. For bipolar depression, a meta-analysis suggested that low-frequency stimulation to the right prefrontal cortex was possibly effective. However, a medium or large sample, randomized, double blind, sham controlled study has not yet been performed.ObjectiveTo examine the efficacy and safety of 1-Hz rTMS to the right prefrontal cortex in patients with treatment-resistant bipolar depression. rTMS was approved by the Ministry of Health, Labor, and Welfare as a highly advanced medical technology on March 1, 2019.MethodsIn this multicenter, double-blind, randomized, sham stimulation-controlled trial for bipolar depression, patients will be individually allocated to active or sham stimulation plus usual medication and followed up for 6 months. The conditions of stimulation by the Mag Pro R30 transcranial magnetic stimulation device (Magventure) will be a frequency of 1-Hz, intensity of 120% motor threshold, and duration of 1800 seconds to the right prefrontal cortex 5 days a week for 4 weeks during the acute treatment period. The primary endpoint will be a total change in the Montgomery-Åsberg Depression Rating Scale score during the acute treatment period.DiscussionThe outcomes of this study will inform clinical practice for the treatment of bipolar depression.Clinical trial registrationhttps://jrct.niph.go.jp/latest-detail/jRCTs032180138, identifier jRCTs032180138.